Coeficientes de uniformidade: sensibilidade a mudanças nos fatores operacionais - Rodrigues, Lineu Neiva; Mello, Jorge L. Pimenta; Mantovani, Everardo C.; Ramos, Márcio M. (IRRIGA, 1997)
Coeficientes de uniformidade: sensibilidade a mudanças nos fatores operacionais